FAKTOR â FAKTOR YANG MEMPENGARUHI PEMILIHAN BIKE SHARING SEBAGAI MODA FEEDER DI KAWASAN BERORIENTASI TRANSIT DUKUH ATAS DALAM KONTEKS PANDEMI COVID-19 - Mayang Larasati, Gabriella
The designation of the Dukuh Atas area as a transit oriented development (TOD) area is expected to be a solution to transportation problems in Jakarta which can reduce dependence on private vehicles, increase the use of public transport and nonmotorized vehicles through developing environmentally friendly activities in areas with high building density and mixed land use as well as transit nodes that are within pedestrian reach. The integration of public transport with non-motorized vehicles such as bicycles in the TOD Dukuh Atas area is the key to addressing first mile last mile problems, such as the distance to transit nodes which are quite far or inadequate connectivity which causes low interest in using public transportation. One form of innovation in the integration of bicycles as non-motorized vehicles with public transportation is by providing a bike sharing service that acts as a first mile last mile feeder mode. In providing bike sharing services, it is also necessary to pay attention to efforts to prevent the risk of Corona virus transmission in the current pandemic conditions, which need adjustments to service operations both from the operator and user side. The purpose of this study is to analyze the factors that influence the choice of bike sharing as a feeder mode in the Dukuh Atas TOD Area in the context of the COVID-19 pandemic so that efforts can be made to maximize the role and function of bike sharing as a choice of feeder mode in the Dukuh Atas TOD Area. . This study uses data from a questionnaire survey with a stated preference approach which is then processed using binomial logit analysis and sensitivity analysis. Based on the results of the study, it is known that the time to switch modes, the integration of rates, security, comfort, and safety are factors that influence the choice of bike sharing mode with the probability of using bike sharing that is obtained at 83.19%. Based on the results of the sensitivity analysis, several interventions can be carried out on the factors that influence the choice of mode in order to increase the probability of using bike sharing.